Aktivitas Antibakteri Nanoemulsi Kombinasi Minyak Sereh (Cymbopogon citratus (DC.) Stapf) dan Minyak Kemangi (Ocimum basilicum L.) terhadap Staphylococcus aureus: Antibacterial Activity of Nanoemulsion of Lemongrass Oil (Cymbopogon citratus (DC.) Stapf) and Basil Oil (Ocimum basilicum L.) Combination against Staphylococcus aureus - Hasan, Nuradnin; Mulyaningsih, Sri; Setianto, Arif Budi (Jurnal Sains dan Kesehatan, 2024)
Lemongrass oil (Cymbopogon citratus (DC.) Stapf) and basil oil (Ocimum basilicum L.) are secondary metabolites that can be utilized as antibacterials. This study aims to determine the antibacterial activity of nanoemulsion preparation formulations of a combination of lemongrass oil and basil oil against S. aureus bacteria and determine the effective concentration of the mixture of the two. Both oils used were verified including GC-MS analysis, specific gravity, refractive index, solubility in alcohol and acid number. The nanoemulsion preparation formulation contained 4% (v/v) combination of lemongrass oil and basil oil, each fraction consisting of F1 (1:3), F2 (2:2) and F3 (3:1). The resulting preparation was tested for physical properties including organoleptic, homogeneity, viscosity, particle size, pH, irritation test, hedonic test and antibacterial activity test using the pitting diffusion method. The results of GC-MS analysis, lemongrass oil has the main compound components, namely E-citral (38.49%) and Z-citral (25.26%) while basil oil has the main compounds, namely Methyl chavicol (58.14%) and linalool (31.72%). Evaluation of the physical properties of lemongrass oil and basil oil roll-on deodorant preparations met the parameters in accordance with the standard. From the results of the antibacterial activity test for S. aureus, F1 had an inhibition zone of 11.44 ± 2.51 mm, F2 18.89 ± 1.05 mm both included in the strong category and F3 23.78 ± 1.72 mm included in the very strong category. The positive control had a zone of inhibition of 10.56 ± 0.53 mm and the negative control had a zone of inhibition of 0 mm. In conclusion, F3 formulation of roll on deodorant preparation with a combination of lemongrass oil and basil oil (3:1) at 4% has effective antibacterial activity against S. aureus bacteria. Keywords:          Lemongrass oil and basil oil, nanoemulsion preparation, S. aureus   Abstrak Minyak sereh (Cymbopogon citratus (DC.) Stapf) dan minyak kemangi (Ocimum basilicum L.) adalah minyak esensial yang dapat dimanfaatkan sebagai antibakteri. Penelitian ini bertujuan untuk mengetahui aktivitas antibakteri formulasi sediaan nanoemulsi kombinasi minyak sereh dan minyak kemangi terhadap bakteri S. aureus dan mengetahui konsentrasi yang efektif dari campuran keduanya. Kedua minyak yang digunakan diverivikasi meliputi analisis GC-MS, bobot jenis, indeks bias, kelarutan dalam alkohol serta bilangan asam. Formulasi sediaan nanoemulsi mengandung 4% (v/v) kombinasi minyak sereh dan minyak kemangi yang masing-masing fraksinya terdiri dari F1 (1:3), F2 (2:2) dan F3 (3:1). Sediaan yang dihasilkan diuji sifat fisik antara lain organoleptik, homogenitas, pH dan aktivitas antibakteri dengan menggunakan metode difusi sumuran. Hasil analisis GC-MS, minyak sereh memiliki komponen senyawa utama yaitu E-sitral (38,49%) dan Z-sitral (26,25%) sedangkan minyak kemangi senyawa utamanya yaitu Methyl chavicol (58,14%) dan linalool (31,72%). Evaluasi uji sifat fisik sediaan nanoemulsi minyak sereh dan minyak kemangi memenuhi parameter yang sesuai dengan standar. Dari hasil uji aktivitas antibakteri S. aureus F1 memiliki zona hambat sebesar 11,44 ± 2,51 mm, F2 18,89 ± 1,05 mm keduanya termasuk kategori kuat dan F3 23,78 ± 1,72 mm termasuk kategori sangat kuat. Kontrol positif mempunyai zona hambat 10,56 ± 0,53 mm dan kontrol negatif memiliki zona hambat 0 mm. Kesimpulannya, formulasi F3 sediaan deodoran roll on kombinasi minyak sereh dan minyak kemangi (3:1) sebanyak 4% memiliki aktivitas antibakteri terhadap bakteri S. aureus yang efektif. Kata Kunci:         Minyak sereh dan minyak kemangi, sediaan nanoemulsi, S. aureus